Smart Efficiency Tracking for Novel Switch—LLC Converter for Battery Charging Applications - Eser Çalışkan; Ozgur Ustun (Energies, 2022)
In this study, a novel smart efficiency tracking (SET) algorithm for GaN-based LLC resonant converter for quick battery charging of light electric vehicles is proposed. Conventional frequency modulation (FM) method, single pulse width modulation method (S-PWM) and discontinuous operation mode method (DOM) are used to track the converter efficiency which varies for different loading conditions during the battery charging process. First, the charging modes are explained to define the efficiency variation clearly. Then, the theoretical background of GaN-based LLC resonant converter is presented and the details of design study are given. Third, the principles of three different switching control strategies, the modeling study and the simulation results are put forward. Finally, the details of the implementation of three different switching strategies are presented for the validation of the study. Furthermore, the implementation of the design and its impact on battery charging are discussed. The proposed efficiency tracking method is validated with a 20% efficiency increase for the low loading conditions of GaN-based LLC converter.